ASSESMENT OF PUBLIC PERCEPTION ON DESIGNING COLOMBO MUNICIPAL COUNCIL AREA AS A GREEN CITY - Ruzaik, Fareena (National Institute of Disaster Management New Delhi, India, 2021)
The Colombo Municipal Council area shows a significant trend on increasing urbanization rate and development every year. However, the current high urbanization rate of Colombo municipal council area and its impacts, reduce green spaces gradually and remarkably. As a result, various socials, health and ecological problems have arisen. In order to escape from these problems, it is recommended to transform the Colombo municipal council area into a green city. So, this study explores the Public Perception on Designing Green City in Colombo municipal council area and investigate the problems and challenges faced by the public due to the Current City Structure. A questionnaire was provided to obtain perceptions from 140 respondents randomly chosen from residents living in the study area. Further secondary data were also has used in this study. 93.3% respondents of the questionnaire had at least medium knowledge of green cities and 92% respondents had at least medium knowledge of sustainable development. The results indicate, due to the current city structure of Colombo municipal council area 76.9% people feel respiratory problems and 78.6% feel excessive heat and consequent massive attitudinal and behavioral changes. 92.9% people also experience depression and irritability. As a result, 100 percent of the people have expressed their desire to transform the Colombo municipal council area into a green city. In other hand, only 79% of them think that transforming the Colombo municipal council area into the green city is a possible sight. In contrast, 21 % of those surveyed said it would be impossible to turn the Colombo municipal council area into a green city. The reasons stated for this are political interference, overcrowding in small areas, improper constructions and ambiguity for most of the general public. However, it has become imperative to build the Colombo municipal council area as a green city by overcoming above obstacles. Therefore, based on this study, utilization of public transport, use of eco-friendly vehicles, planting suitable trees on both sides of roads, paths and highways, planting of eco-friendly plants in terraced floors, introducing green city building methods during building construction, carrying out proper waste disposal projects were identified as some possible ways to design the Colombo Municipal Council area as a green city.
Assessment of public perception on designing Colombo Municipal Council area as a Green City, International conference- (online) Challenges of Disasters: Vulnerability, Adaptation and Resilience, collaboration of National Institute of Disaster Management & Regional Remote Sensing Center- New Delhi, India.
Keywords: Urbanization, Green cities, Sustainable development, Public awareness, Green activities.